PLANNING OF THE NEED IN TECHNICAL SUPPLY OF PROJECTS OF GRAIN, OIL AND LEGUME CROPS HARVESTING OPERATIONS - Сидорчук, Олександр Васильович; Тригуба, Анатолій Миколайович; Панюра, Ярослав Йосипович; Сидорчук, Леонід Леонідович; Березовецький, Сергій Андрійович; Скібчик, Володимир Іванович (Eastern-European Journal of Enterprise Technologies, 2013)
The paper states that effective managements of projects of grain, oil and legume crops harvesting operations needs developing a single method of the need in technical supply of these project. It proves the idea that planning of the need in technical supply of the project of early oil, legume and grain crops harvesting, anyway, stems from the results of forecasting the major factors of the inner project environment. The research suggests its method of planning of the need in technical supply of grain, oil and legume crops harvesting projects which is a core of automated informational and analytical system of forecasting a need in technical supply of these projects implementation. Method of planning the need in technical supply is based upon a criterion of timely harvesting operations on some fields of the seasonal programme.